Produktivitas Getah Pinus (Pinus merkusii) pada Berbagai Diameter Batang (Studi Kasus di Hutan Lindung Gn Manglayang, BKPH Manglayang Barat Perum Perhutani Divre III Jabar Banten) - Irawan, Guntur; Darliana, Ina; Solihat, Raizal Fahmi (Fakultas Kehutanan Universitas Winaya Mukti, 2024)
The object of research is to examine the effect of various diameter on the productivity of pine resin (Pinus merkusii) in the Gunung Manglayang Protected Forest. The research was conducted in the protected forest area of compartment 43G RPH Arcamanik BKPH Manglayang Barat, Perum Perhutani KPH Bandung Utara, using a Completely Randomized Design (CRD) with four diameter classes of trees: 20–25 cm, 30–35 cm, 40–45 cm, and 50–55 cm. Each diameter class consisted of 5 trees, with 5 repetitions of resin tapping. The results showed that pine resin productivity increased with the growth of stem diameter. The 20–25 cm diameter class produced 18.55 grams/tree/7 days, while the 50–55 cm diameter class produced 30.89 grams/tree/7 days. The analysis of variance (ANOVA) showed that tree diameter had a significant effect on resin productivity (Sig. = 0.000). The Duncan’s multiple range test further confirmed that the 50–55 cm diameter class yielded the highest resin productivity. In conclusion, the larger the stem diameter, the higher the resin productivity. Therefore, tapping should be carried out on trees with a minimum diameter of 20 cm to achieve optimal results without damaging tree growth.Keywords: Resin productivity, Pinus merkusii, various diameter